2018
DOI: 10.4314/jae.v22i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing maize production in Sikasso Region of Mali

Abstract: This study examined the contribution of subsidized inputs to farmers' level of maize production in Sikasso region of Mali. A multistage sampling procedure was used to select 200 beneficiaries of input subsidy for this study. Structured questionnaires were used to collect data which were analysed using descriptive and inferential statistics such as Chi-square, Pearson Product Moment Correction (PPMC), ANOVA and regression at 0.05 significant level. Results reveal beneficiaries' mean age to be 48.50 years. Almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Many factors might have contributed to this. Similar findings were reported by Epule et al (2021), Justin (2015) and Yassoungo et al (2018) who found that income from maize production is generally low is low.…”
Section: Farm Incomesupporting
confidence: 89%
See 1 more Smart Citation
“…Many factors might have contributed to this. Similar findings were reported by Epule et al (2021), Justin (2015) and Yassoungo et al (2018) who found that income from maize production is generally low is low.…”
Section: Farm Incomesupporting
confidence: 89%
“…Despite the evident role of maize production among the smallholder farmers, past studies have reported that its farm income is low especially in developing countries (Epule et al, 2021;Justin, 2015;Yassoungo et al, 2018). This discourages farmers from engaging in continuous maize production, a situation that is not good for the country's economic development, poverty alleviation and food security goals.…”
Section: Introductionmentioning
confidence: 99%
“…The study findings indicated that the educational attainment of household heads had a statistically significant effect on maize production. In a study conducted by Yassoungo (2018), it was discovered that 63.5% of the participants did not have any formal education, 24% had never received any type of education, and the remaining 12.5% had acquired a formal education According to the findings of Yassoungo ( 2018), a proportion of the participants (63.5%) lacked formal education, while 24% had not attended any educational institution. The remaining 12.5% possessed formal education.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%